(untitled) (Agriculture, Food, and Natural Resources Journal, 2024)
One of the most abundant and versatile natural resources is wood. Due to its numerous uses, the demand for wood is growing faster than the supply in many developing countries. Selected wood physical and mechanical properties of Douglas Fir wood was evaluated in this study to meet the need of wood for various applications. Wood samples from Ido Local government of Oyo State were obtained from (base, middle, top) and (compression and normal wood side) of a 9-years old main stem for moisture content, wood density and mechanical properties. Data obtained were statistically analyzed and result revealed that moisture contents at the level of stem (base 64.01%, middle 70.02% and top 70.02%) increased from base to top, inversely in Density decreased from base 442.60kg/m3, middle 404.04kg/m3 to top 388.20kg/m3. At type of wood (Normal and compression wood), moisture contents are 66.35% and 69.82% and Densities are 421.01kg/m3 and 402.22kg/m3 respectively. Modulus of Elasticity with mean value of 10850 N/mm2, showed decreased from base 11078.26mm2 to top 10719.91N/mm2. Modulus of Rupture decreased from base 92.62N/mm2, to top 88.82N/mm2, average value of 90.09N/mm2. With the average value 55.07 N/mm2, Compressive strength parallel to the grain also decreased from base 55.07N/mm2 to top 51.24N/mm2. All wood properties studied showed that Douglas fir wood can be classified as a medium density wood, suitable for medium construction such as cabinet work, veneer etc and therefore substitute the most used species and reduce overexploitation of wood.